Diseño e implementación de un módulo prototipo de pruebas con diagnóstico de problemas, para motores trifásicos de inducción, en la Empresa Pública Metropolitana de Transporte de Pasajeros - Vásquez Tulchan, Daniel Alejandro (2016)
This project arose in the Public Company Metropolitan Transport of Passengers, which proposed the feasibility and implementation of a test bench for electric motors of the trolleybus with a power rating of 230 kW. The maintenance of these engines entails the loss of money in the disassembly and assembly, therefore needed to verify faults and damage before installation on the unit trolleybus. For reasons of time and annual budget of the company, it was agreed that the design and implementation of a prototype module tests with troubleshooting for lower power induction motors, used in fans with rated power 1.1 kW and less to this. The testing prototype module design can be scaled to the maintenance of engines of higher power, with the ease of understanding of control and diagnostic electro mechanical. This account with a web application HMI, to control and verify the fault diagnosis and give possible solutions quickly and compact, fulfilling the maintenance plan established in the company. The expectations of this project are intended to the maintenance of three-phase induction motors in the Ecuadorian industry, due to the great demand for industrial processes linked to this type of engines, adding technology of easy access and control as: speed, scalability, remote access, visualization of damage and records. In order to comply with the maintenance plan.